2021
DOI: 10.1080/14643154.2021.1885576
|View full text |Cite
|
Sign up to set email alerts
|

Nothing about us without us: Deaf education and sign language access in China

Abstract: This empirical qualitative study aims (1) to understand the Chinese context in promoting accessible high-quality education for deaf communities and (2) to create an opportunity for deaf experts to contribute to sign language research, instruction, interpreting programmes, and deaf education in China. Using a focus group methodology, we gathered data from 48 participants from four different stakeholder groups (10 teachers, 16 administrators/researchers, 6 interpreters, 16 community members) identifying concerns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…The World Federation of the Deaf (WFD) is a global organization led by the deaf, and their vision is to promote the human right to sign language for all deaf people, i.e., to ensure equal rights for over 70 million deaf people worldwide [33,34]. In Serbia alone, around 150,000 people with hearing impairment are registered [9].…”
Section: Discussionmentioning
confidence: 99%
“…The World Federation of the Deaf (WFD) is a global organization led by the deaf, and their vision is to promote the human right to sign language for all deaf people, i.e., to ensure equal rights for over 70 million deaf people worldwide [33,34]. In Serbia alone, around 150,000 people with hearing impairment are registered [9].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, these results could be included in a broad social and cultural perspective that includes the relationship between people who are deaf and hearing individuals, in which the use of sign language interpretation could be fundamental. For instance, in a study by Jones et al [ 43 ], participants reported feeling more included and valued when sign language interpretation was provided at social events, and additionally, hearing people who had previously felt uncomfortable interacting with people who were deaf reported feeling more confident and at ease when they were able to communicate through a sign language interpreter. Furthermore, another important factor in building relationships between the deaf and hearing communities is education.…”
Section: Discussionmentioning
confidence: 99%
“…Among these inputs, whether facial and bodily expressions, gestures, or postures are typically available for deaf individuals in social contexts, sign language is usually restricted to deaf communities. In light of this, promoting learning of sign language in hearing individuals, as well as providing salient visual cues in social situations, would facilitate social inclusion of deaf individuals (Jones et al, 2021)…”
Section: General Conclusionmentioning
confidence: 99%
“…Among these inputs, whether facial and bodily expressions, gestures, or postures are typically available for deaf individuals in social contexts, sign language is usually restricted to deaf communities. In light of this, promoting learning of sign language in hearing individuals, as well as providing salient visual cues in social situations, would facilitate social inclusion of deaf individuals (Jones et al, 2021 ). It is therefore particularly important to support the development of inclusive guidelines for everyday social contexts (e.g., Santos & Portes, 2019 ; for a practical guide in scholar settings, see Alasim, 2018 ; for work settings, see Foster & MacLeod, 2003 ).…”
Section: General Conclusionmentioning
confidence: 99%